’Towards a Warmer World: What climate change will mean for New Zealand’s future’ and ’Time of Useful Consciousness: Acting urgently on climate change’ - Gregory, Geoff (New Zealand Science Review, 2015)
​These two books are in the series from Bridget Williams Books entitled BWB Texts, described as ‘short books on big subjects from great New Zealand writers’. They complement each other in describing what climate change will mean for our future and what actions are needed now to reduce the causes and mitigate the effects of climate change.